Understanding Employee Productivity Through Digital HRM and Self-Efficacy: Evidence from Banking Employees - Dodi Saputra Chairullah; Marlinda Waty; Nurlia Nurlia; Tutik Yuliani (Journal of Marketing Management and Innovative Business Review, 2026)
The banking industry is experiencing rapid digital transformation, encouraging organizations to adopt Digital Human Resource Management (Digital HRM) practices to enhance employee performance and organizational effectiveness. This study aims to examine the effect of Digital HRM on employee productivity and investigate the mediating role of self-efficacy among banking employees in Balikpapan City, Indonesia. A quantitative approach was employed using survey data collected from 100 banking employees selected through purposive sampling. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). The findings reveal that Digital HRM has a positive and significant effect on employee productivity. Furthermore, Digital HRM significantly enhances employees’ self-efficacy, which in turn positively influences employee productivity. The mediation analysis confirms that self-efficacy significantly mediates the relationship between Digital HRM and employee productivity. These results support Social Cognitive Theory by demonstrating that organizational digital resources contribute to improved employee outcomes through psychological mechanisms. The study provides practical implications for banking institutions by highlighting the importance of integrating digital HR practices with initiatives aimed at strengthening employee confidence and capability in utilizing digital technologies. Ultimately, effective Digital HRM implementation can serve as a strategic tool for improving workforce productivity in the banking sector.